Investigating resource productivity: the ecological potential of printed electronics as alternative to PCB - Marieke van Diemen; Jan Brusselaers; Corné Rentrop (Environmental Research Communications)
Printed electronics are gaining momentum as an alternative to etched electronics. Production of printed electronics requires less energy, water and raw materials and its flexible, transparent, stretchable and breathable potential allows for numerous new applications. While still in its infancy, printed electronics have the potential to become a permanent low-cost and efficient substitute for conventional production methods. However, despite promising assets of the printed electronics technology, few quantitative environmental analysis have been performed comparing printed electronics to the conventional printed circuit board (PCB). To fill this gap in the literature, this research evaluates and compares PCB circuitry production to that of a common printing technology; screen printing. A combination of a resource productivity and pollution intensity evaluation and a material input and output analysis is performed. Performance is evaluated by gathering data from existing literature, expert consultancy and own calculations on production data and product weight. Printed electronics were evaluated according to a worst-case scenario and PCB to a best-case scenario in terms of resource consumption. The findings reveal substantial disparities in resource productivity and pollution intensity between printed electronics and PCB. Printed electronics demonstrate superiority across all indicator ratios in comparison to PCB as a consequence of - for example - a zero-water production process, or a printed solution which is 16.14 times lighter in terms of weight. This research thereby contributes to informing the electronics sector about a promising alternative to PCB from the perspective of resource efficiency and pollution intensity. As such, our research results provide a lever for future research investigating the scalability and profitability of the implementation of this technology.